The Narrative of Democracy in Classical Arabic Literature: According to Ibn al-Daya in al-Mokafat - Delshad, Sharam (UIN Raden Mas Said Surakarta, 2023)
This study explores the complexity and narrative of democracy in classical Arabic literature through the lens of Ibn al-Daya's